Bronze Age tell communities in context : an exploration into culture, society and the study of European prehistory. - Kienlin, Tobias L., (Archaeopress archaeology., 2015)
This study challenges current modelling of Bronze Age tell communities in the Carpathian Basin in terms of the evolution of functionally-differentiated, hierarchical or 'proto-urban' society under the influence of Mediterranean palatial centres.